Glucose Synthesis from Imperata Cylindrica by Acid Hydrolysis Process - Muhammad Ashfal Ashfiya; Ahmad Rizky Safrudin; Ni Ketut Sari; Rachmad Ramadhan Yogaswara (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Imperata cylindrica, commonly known as alang-alang, is a fast-growing, abundant, and underutilised grass often considered a weed. However, its high cellulose content makes it a promising lignocellulosic biomass for renewable glucose production. This study explores the synthesis of glucose from Imperata cylindrica through acid hydrolysis, with the aim of utilizing this low-cost biomass as a sustainable raw material for bio-based products. The hydrolysis process was investigated using two main variables: hydrolysis time (1, 1.5, 2, 2.5, and 3 hours) and acid concentration (1%, 1.5%, 2%, 2.5%, and 3%). The resulting hydrolysates containing glucose were analyzed using a refractometer, UV-Vis spectrophotometer, and further optimized using Response Surface Methodology (RSM). The highest glucose content obtained by refractometer was 6.5%, while RSM predicted a maximum of 6.49%, and UV-Vis analysis showed 6.34%. All optimal results were achieved under the condition of 2.5 hours of hydrolysis time and a 3% acid concentration. These findings highlight the potential of Imperata cylindrica as a viable and sustainable feedstock for glucose production through acid hydrolysis, contributing to the development of alternative bio-resources. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land